The Effect Of Motivation And Work Environment On The Performance Of Personnel Police Personnel Performance In The Planning Section At Central Lampung Police Station - Junaidi, Junaidi (Social Sciences Journal, 2025)
The research object at the Lampung Tangah Police Station in the planning section is located Jl. Country No.1, Mt. Sugih, District. Mt. Sugih, Central Lampung Regency, Lampung postal code 34161 This research used a survey by distributing questionnaires in the form of statements with respondents' level of agreement using a Likert scale of 1 to 5 distributed to respondents with a sample size of 27 people consisting of police personnel in the planning section of the Central Lampung Police. Data analysis was carried out using multiple linear regression with the SPSS version of the program. 23. The results of the research show that motivation has a positive effect on the performance of police personnel as evidenced by the R squere correlation coefficient of determination of motivation on the performance of police personnel of 72.1% and based on work environment data it has a positive effect on the performance of police personnel as evidenced by an R.squere of 57.6% change The employee performance variable (bound) can be explained by the work motivation variable. Meanwhile, changes in the dependent variable of personnel performance can be explained by the work environment and motivation variables with simultaneous test results. Motivation and the work environment have a positive and significant effect on personnel performance with an F test result of 74.1. % while the remaining 25.9% is explained by other factors that were not carried out in this research. These other factors include work environment, competence, career development and others.